Effects of Low Pressure of Laparoscopic Cholecystectomy on Arterial Pressure of Carbon Dioxide and Mean Blood Pressure - Nematihonar, Behzad; Malekpour, Nasser; Hashemian, Morteza; Jalaeifar, Amirhosein; Mirkheshti, Alireza; Sayadi, Shahram (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: The effect of low pressure pneumoperitoneum in laparoscopic cholecystectomy on partial pressure of carbon dioxide in the arterial blood (PaCO2) is an important subject which has not been completely defined. Methods: In a double-blind clinical trial, we randomly studied 202 ASA (The ASA physical status classification system) class 1, 2 patients aged between 20 and 85 years who were candidates for elective laparoscopic cholecystectomy. They were randomly divided into two groups of low pressure pneumoperitoneum (6-8 mm Hg) and standard pressure pneumoperitoneum (12-14 mm Hg). By the same general anesthesia protocol in the two groups, PaCO2 was assessed before CO2 insufflation and desufflation. Mean Arterial blood Pressure (MAP) was measured in the two groups. Results: PaCO2 was not significantly different between the 2 groups before CO2 insufflation. But, PaCO2 was statistically lower in low pressure pneumoperitoneum group before CO2 desufflation (P= 0.001). Mean Arterial Pressure (MAP) in standard pressure pneumoperitoneum group was lower than the low pressure pneumoperitoneum group at 5 and 10 minutes after CO2 insufflation and before the time of CO2 desufflation (P=0.001, P=0.006 and P=0.001, respectively). While, MAP was not statistically different between the two groups before CO2 insufflation (P=0.55). Conclusion: Low pressure pneumoperitoneum during laparoscopic cholecystectomy can be an effective protocol to prevent the rise of PaCO2 by preserving the hemodynamic status in such cases.